Determination of Postprandial Glycemic Responses by Continuous Glucose Monitoring in a Real-World Setting - Röhling, Martin (Nutrients, 2019)
Background: Self-monitoring of blood glucose using capillary glucose testing (C) has a number of shortcomings compared to continuous glucose monitoring (CGM). We aimed to compare these two methods and used blood glucose measurements in venous blood (IV) as a reference. Postprandial blood glucose levels were measured after 50 g oral glucose load and after the consumption of a portion of different foods containing 50 g of carbohydrates. We also evaluated the associations between postprandial glucose responses and the clinical characteristics of the participants at the beginning of the study. Methods: 12 healthy volunteers (age: 36 ± 17 years, BMI: 24.9 ± 3.5 kg/m(2)) ate white bread (WB) and whole grain (WG) bread and drank a 50 g glucose drink as reference. Postprandial glucose responses were evaluated by CGM, IV and C blood glucose measurements. Incremental area under the curve (AUC(i)) of postprandial blood glucose was calculated for 1 h (AUC(i 0-60)) and 2 h (AUC(i 0-120)). Results: After the consumption of white bread and whole grain bread, the AUC(i 0-60 min) did not differ between CGM and IV or C. AUC(i 0-120 min) of CGM showed no difference compared to C. Correlation analyses revealed a positive association of age with glucose AUC(i 0-120) (r = 0.768; P = 0.004) and WG AUC(i 0-120) (r = 0.758; P = 0.004); fasting blood glucose correlated with WG AUC(i 0-120) (r = 0.838; P < 0.001). Conclusion: Despite considerable inter-individual variability of postprandial glycemic responses, CGM evaluated postprandial glycemic excursions which had comparable results compared to standard blood glucose measurements under real-life conditions. Associations of AUC(i 0-60) and AUC(i 0-120) postprandial glucose response with age or fasting blood glucose could be shown.